Contribution of colony-stimulating factor 1 to neuropathic pain - Xiaobing Yu (PAIN Reports, 2021)
Abstract. Molecular and cellular interactions among spinal dorsal horn neurons and microglia, the resident macrophages of the central nervous system, contribute to the induction and maintenance of neuropathic pain after peripheral nerve injury. Emerging evidence also demonstrates that reciprocal interactions between macrophages and nociceptive sensory neurons in the dorsal root ganglion contribute to the initiation and persistence of nerve injury-induced mechanical hypersensitivity (allodynia). We previously reported that sensory neuron-derived colony-stimulating factor 1 (CSF1), by engaging the CSF1 receptor (CSF1R) that is expressed by both microglia and macrophages, triggers the nerve injury-induced expansion of both resident microglia in the spinal cord and macrophages in the dorsal root ganglion and induces their respective contributions to the neuropathic pain phenotype. Here, we review recent research and discuss unanswered questions regarding CSF1/CSF1R-mediated microglial and macrophage signaling in the generation of neuropathic pain.